Seroprevalensi Penyakit Egg Drop Syndrome pada Itik di Desa Tumbak Bayuh, Kecamatan Mengwi, Badung, Bali - Gusti Ayu Yuniati Kencana; I Made Kardena; Ni Wayan Apsari Shantika Pratistha (Jurnal Sain Veteriner, 2019)
Egg Drop Syndrome can cause detrimental impacts on breeders due to reducing production and quality of theaffected eggs.This study aim was to determine the seroprevalece ofantibody against Egg Drop Syndrome (EDS) virus in ducks. Antibody titers examination was done from 75blood samplesof ducks thathave not been vaccinatedagainstEDS virus. The duck samples were collected from Tumbak Bayuh Village, Mengwi, Badung. Serological examination was held at the Virology Laboratory,Faculty of Veterinary Medicine, Udayana University by usingHaemagglutination Inhibition (HI) test. HI test results showed that 24 samples were positive contained antibody of the EDS,while 51 samples were negative. Range of EDS antibody titer observed was from24 to 27 HI units.  This results indicates that the ducks have protective antibody titer against EDS virus. The positive serum samples were also tested using HI test against Newcastle Disease (ND) virus with negative result. It can be concluded that the ducks in Tumbak Bayuh Village, Mengwi, Badung have 32% of antibody titer against EDS virus whichmight result from being exposed by EDS virus naturally.